Practical Partner Selection of Chip-Interleaved Decode and Forward Cooperation in WSNs Subject to Frequency-Selective Fading - Tian, Jianjie; Berber, Stevan; Zhang, Lei (Wireless personal communications, 2021)
This paper has investigated the feasibility of deploying a decode and forward (DF) cooperative protocol and a chip-interleaving signal processing in combination as a practical energy-saving technique to prolong the lifetime of WSNs operating over AWGN channels subject to frequency-selective Rayleigh fading. This work firstly aims to quantify the BER performance of a chip-interleaved DF (CIDF) cooperation in WSNs. Following, it is extended to analyze an energy efficient CIDF cooperation from the perspective of optimally distributing the transmit power and choosing an ideal cooperating node. Finally, Matlab evaluations of theoretical findings have been provided. Results indicate that the proposed partner selection rules are computationally efficient, and can be easily used by sensor nodes to improve the system’s energy efficiency effectively.